Physical performance changes after unsupervised training during the autumn/spring semester break in competitive tennis players - Kovacs, M. S.; Pritchett, R.; Wickwire, P. J.; Green, J. M.; Bishop, P. (British Journal of Sports Medicine, 2007)
Background: All competitive tennis players take time away from coaches throughout the year; however, little information is available as to the short-term physiological effect of these breaks.